Strategic marketing decision-making in Japanese and South Korean companies - Lee, Yang-Im (Chandos Asian studies series., 2008)
This book acts as a bridge between marketing and strategic management, as it is written from a strategic marketing perspective. It provides students and practising managers with an appreciation and an understanding of how managers in Japanese and South Korean companies formulate and implement strategic marketing decisions, how they embrace the organizational learning concept, and how they formulate working relationships with staff in partner organizations. It provides an explanation of the role that culture plays in the management process and various problems are cited in the text and solutions are offered that reinforce the theories and concepts covered. A number of case studies highlight the link between theory and practice, and the work is structured in a way that allows the reader to think through and reflect upon the key issues associated with decision-making within Japanese and South Korean companies. The work is academically underpinned and contains relevant insights for practising managersThe authors draw upon their marketing and management knowledge and expertise in order to contribute to a developing body of general management theoryThe methodological approach outlined in the book will facilitate a deeper understanding of how national cultural value systems are linked with organizational cultural value systems, and this will enhance interdisciplinary research approaches.